Analisa Efektivitas Waktu Penerapan Metode NSC dan SBO Pada Proyek Renovasi Interior Retail di STAR Department Store Summarecon Bekasi - Putranto, Dwi; Putra, Bramanta Octa Danu (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This research aims to provide education in the analysis process to understand the effectiveness of package classification in the implementation of retail business interior project, namely, Star Department Store. By making a short conctact approach through the Nominated Subcontractor (NSC) and Supply by Owner (SBO) contract. Both contracting methods cane have a very significant impact on project completion, which can result in time efficiency, leading to quality outcomes. The NSC method can provide appropriate directions from subcontractors to complete specific tasks according to established requirement. The SBO method can give project owners the opportunity to manage the procurement of materials or equipment directly in implementing the retail business interior project. This research can provide comprehensive information on the structutured work package classification that can enhance project effectiveness throught both the contracts. The research approach used is a case study with qualitative analysis on several retail business interior projects that use NSC and SBO contracts. The results of this study can show the role of conducting a clear classification of interior design management project work packages carried out with proper management based on NSC or SBO contracts can improve cost efficiency, quality, and time for completing the STAR Department Store retail business interior renovation project.